Intelligent system for weeds management in pineapple crop with precision agriculture concepts - JIMÉNEZ LÓPEZ, ANDRÉS FERNANDO; CAMARGO PICO, DIANA ANDREA; García Ramírez, Dayra Yisel (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The aim of precision agriculture is to apply agricultural inputs in the right place, time and amount. The site-specific weed management is a precision agriculture strategy that allows reducing the herbicide application, minimizing inputs costs, with positive effects for the environment. The objective of this paper is to show the advances in the development of weed detection and herbicide application system for a pineapple crop, using precision agriculture concepts. The prototype uses an artificial vision system for acquisition of reflectance in plants in the visible spectrum and an embedded system that allows the image processing in real-time as a weed detection mechanism. The prototype has an automatic fumigation system, that emulates the selective herbicide application, which together is implemented above a terrestrial vehicle that travels into the pineapple crop rows. The weed detection algorithm for pineapple had an efficiency major than 80%, obtaining satisfactory outcomes and the fulfilment of the requirements for the weed detection and input application only in the places where it is necessary.